Utilization of Olive Pulp in Broiler Rations - E. Rabayaa; J. M. Abo Omar; R. A. Othman (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This research was conducted to study the effects of different levels of olive pulp on body weight gain, feed intake and feed conversion efficiency of broiler chicks. A total of 160 day-old chicks were used in this research and were divided into five experimental groups with four replicates in each. Olive pulp was incorporated in four of the experimental groups at rates of 2.5, 5, 7.5 and 10% in both starter and finisher feeds to replace similar rates of yellow corn. Chicks were fed these diets during the entire feeding trial which lasted for 35 days. Weight gain of chicks was the same in chicks consuming up to 7.5% of olive pulp. However, weight gain of chicks fed the level of 10% olive pulp had the lowest significant (p